2016
DOI: 10.4236/wja.2016.61003
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of the Ideology of Monogamy’s Influence on HIV Epidemiology

Abstract: The linked ideas that all members of society should only engage in monogamous relationships and that these should all be based on romantic love are decided outliers from a historical perspective. Despite this, there is a widespread contemporary belief that monogamy based on love is the most ethical and natural form of partnering for humans-mononormativism. It has long been accepted that our values influence how we frame and interpret scientific questions. In the article we ask, using the example of mononormati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A particularly striking finding of this study was that for both men and women the population distribution of C-IATs followed a normal distribution with 92.3% of the sample revealing an implicit preference for monogamy. This is perhaps not a surprising finding given that until recent times any form of non-monogamy was proscribed and stigmatized in Western Europe [ 71 – 73 ]. It would therefore be instructive to reproduce this study in populations in regions such as sub-Saharan Africa, which have histories of greater tolerance to various forms of concurrent partnering [ 27 , 53 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A particularly striking finding of this study was that for both men and women the population distribution of C-IATs followed a normal distribution with 92.3% of the sample revealing an implicit preference for monogamy. This is perhaps not a surprising finding given that until recent times any form of non-monogamy was proscribed and stigmatized in Western Europe [ 71 – 73 ]. It would therefore be instructive to reproduce this study in populations in regions such as sub-Saharan Africa, which have histories of greater tolerance to various forms of concurrent partnering [ 27 , 53 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…"Risk perceptions refer to people's beliefs about their vulnerability to danger or harm" [16]. Perception of health risk is a key dimension of most health behavior models [17,18] used to construct health promotion campaigns particularly those targeting HIV-related risk behaviours [19]. "Studies have shown that greater perceived vulnerability to HIV is associated with decreased involvement in risk taking" [20,21].…”
Section: Introductionmentioning
confidence: 99%